(untitled) (Acta Scientiarum. Agronomy, 2026)
The replacement of native vegetation with nonnative vegetation for different land uses, which is a consequence of the intensification and expansion of agricultural production, significantly alters the dynamics of soil organic fractions. The aim of this study was to evaluate the changes in carbon and nitrogen contents and stocks, as well as the chemical fractions of organic matter, caused by different land uses in Cerrado areas. The selected areas were conventional tillage (CTS), no-tillage (NTS), eucalyptus cultivation (EC) and native Cerrado vegetation (NC) in the regions of Barreiras and Luís Eduardo Magalhães, Bahia State, Brazil. The highest carbon contents and stocks were found under NTS up to 10 cm, and these values, as well as those of EC, were equal to those found under NC below 10 cm. The same phenomenon was not verified for the nitrogen contents and stocks in the soil up to 20 cm deep. The values of carbon in the fulvic acid fraction (C-FAF) under NTS and EC were equal to those of NC up to 10 cm deep, but only EC was equal to NC below this layer. At the 10–20 cm depth, the C-FAF increased by 1.23 g kg-1 and 0.95 g kg-1 under NTS compared with those under EC and NC, respectively. With respect to the correlations between carbon fractionation and total organic carbon, the nonextractable humic fraction (C-HUM) had the strongest correlation with the TOC content, with r2 = 96 (p < 0.001). Over time, the input of residues in the NTS and EC areas contributed to increasing soil carbon stocks and organic matter quality, with a recovery of up to 84% of the carbon in humin.